MEASUREMENT OF COMPANY PERFORMANCE IN VARIOUS PERSPECTIVE ASSESSMENTS OF AUTOMOTIVE SUB-SECTOR COMPANIES AND THEIR COMPONENTS LISTED ON THE INDONESIA STOCK EXCHANGE - Ratu Sifa Ni’mah; Rika Kartika (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to empirically prove the influence of financial perspective, customer perspective, internal business process perspective on company performance in the automotive sub-sector and its components listed on the Indonesia Stock Exchange (IDX) for the period 2013-2021. The population of this study were 13 automotive sub-sector companies and its components listed on the Indonesia Stock Exchange (IDX) for the period 2013-2021, and there are 4 samples of companies using purposive sampling technique. The study method is descriptive quantitative. The results of this study can be concluded that partially the financial perspective and customer perspective have a positive and significant effect on company performance, while the internal business process perspective has a negative and significant effect on company performance